2021
DOI: 10.1038/s41598-021-96935-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in AURORA cell cycle kinases are associated with glioblastoma multiforme

Abstract: Glioblastoma multiforme (GBM) is the most frequent type of primary astrocytomas. We examined the association between single nucleotide polymorphisms (SNPs) in Aurora kinase A (AURKA), Aurora kinase B (AURKB), Aurora kinase C (AURKC) and Polo-like kinase 1 (PLK1) mitotic checkpoint genes and GBM risk by qPCR genotyping. In silico analysis was performed to evaluate effects of polymorphic biological sequences on protein binding motifs. Chi-square and Fisher statistics revealed a significant difference in genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It has been shown that single nucleotide polymorphisms in AURKC were associated with cancer risk in both glioblastoma and gastric cancer. 50 , 51 These specific mutations could be used to define M3-like subtype. These results suggested that M3-like and M3 patients were highly similar in terms of GMP-like cells, and the abnormal genomic features were distinct.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that single nucleotide polymorphisms in AURKC were associated with cancer risk in both glioblastoma and gastric cancer. 50 , 51 These specific mutations could be used to define M3-like subtype. These results suggested that M3-like and M3 patients were highly similar in terms of GMP-like cells, and the abnormal genomic features were distinct.…”
Section: Resultsmentioning
confidence: 99%
“…In glioblastomas, aberrant spindle assembly and defects in chromosome segregation have been reported, leading to genomic instability. These defects are often associated with alterations in key spindle regulators and checkpoint proteins, such as Aurora kinases and Polo-like kinases, which are frequently overexpressed or mutated in glioblastoma [28][29][30].…”
Section: Introductionmentioning
confidence: 99%